(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In recent years, more and more people have been pushed to direct usage of various information systems (IS) developed by governmental, commercial, municipal, and non-governmental organisations. IS were widely used already for a relatively long time – 2 or 3 decades (depending of state), however, people were not pushed to use them directly, they were used by staff members of organisations, so for clients it does not made a difference, do they use an IS or, for example, a paper folder or a file cabinet. Now people are increasingly required to use ISs directly, which makes the process more challenging and potentially dangerous. This article aims to analyse this situation and these processes, trying to classify risks, draw conclusions and provide recommendations.